Gender and modern Irish drama - Harris, Susan Cannon (2002)
Introduction: bodies and blood. - Body and soul: Yeats, the Famine, and the two Cathleens. - Under siege: blood, borders, and the body politic. - Excess of love: Padraig Pearse and the erotics of sacrifice. - The body of truth: sensationalism and sacrifice in Sean O'Casey's Dublin trilogy. - Misbirth of a nation: Yeats and the Irish Free State